Stosowanie Karty Praw Podstawowych Unii Europejskiej: Protokół brytyjski i Sprawozdania ze stosowania KPP UE - Księżniakiewicz, Malwina (Wydział Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2012)
The application of the European Union Charter of Fundamental Rights: the British Protocol and the Reports on the Application of the EU Charter of Fundamental Rights The first part of the paper analyzes the content of the British Protocol and the justification for its drafting. It also presents individual standpoints, and in particular Polish responses which triggered a general discussion, as was the case with the Charter of Fundamental Rights. Another part of the paper is devoted to analyzing the Reports on the Application of the EU Charter of Fundamental Rights, published annually since the Chart came into effect in 2010. The reports discuss issues that were successfully resolved, as well as those continuing to pose a challenge for the EU.